Profit Persistence and Stock Returns - Adelina Gschwandtner; Michael Hauser (University of Kent, School of Economics, 2013)
This paper attempts to assemble evidence for the relationship between the product and the financial market. Drawing back on work in industrial organization, we analyze the relationship between profit persistence and expected stock returns. We show that long-run profit persistence together with other additional economic firm fundamentals have a significant impact on stock returns and on their volatility even after adjusting for risk. At the same time we bring evidence for a 'low volatility anomaly'.
Keywords: L10; G11; L25; 330; Profit Persistence; Competition; Stock Return; Heteroscedasticity; Low-Volatility Anomaly; Dividend Discount Model